2007
DOI: 10.1051/0004-6361:20077456
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field dissipation in neutron star crusts: from magnetars to isolated neutron stars

Abstract: Context. We study the non-linear evolution of magnetic fields in neutron star crusts with special attention to the influence of the Hall drift. Aims. Our goal is to understand the conditions for fast dissipation due to the Hall term in the induction equation. We study the interplay of Ohmic dissipation and Hall drift in order to find a timescale for the overall crustal field decay. Methods. We solve numerically the Hall induction equation by means of a hybrid method (spectral in angles but finite differences i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
254
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 200 publications
(260 citation statements)
references
References 40 publications
4
254
1
1
Order By: Relevance
“…The first attempts in this direction used a split approach. Pons & Geppert (2007) studied the evolution of the field by solving the complete induction equation in an isothermal crust, but assuming a prescribed time dependence for the temperature. They found that crustal magnetic fields in NSs suffer significant decay during the first ≈10 6 yr and that the Hall drift, although inherently conservative (i.e., alone it cannot dissipate magnetic energy), plays an important role since it may reorganize the field from the larger to the smaller (spatial) scales where Ohmic dissipation proceeds faster.…”
Section: Magneto-rotational Evolutionmentioning
confidence: 99%
“…The first attempts in this direction used a split approach. Pons & Geppert (2007) studied the evolution of the field by solving the complete induction equation in an isothermal crust, but assuming a prescribed time dependence for the temperature. They found that crustal magnetic fields in NSs suffer significant decay during the first ≈10 6 yr and that the Hall drift, although inherently conservative (i.e., alone it cannot dissipate magnetic energy), plays an important role since it may reorganize the field from the larger to the smaller (spatial) scales where Ohmic dissipation proceeds faster.…”
Section: Magneto-rotational Evolutionmentioning
confidence: 99%
“…The actual mechanisms, causing the magnetic field to change on these rather short timescales, are only poorly understood and there is no definitive answer to the question of which part of the neutron star dominates the magnetic field evolution. Most theoretical studies and numerical simulations focus on the crust as the source of the field decay and neglect the core contribution (Pons & Geppert 2007;Viganò et al 2013;Gourgouliatos & Cumming 2014). However, one could argue that the core, which carries the majority of the star's inertia and magnetic energy, should also play a role in the magnetic field evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, the Meissner-Ochsenfeld effect prevents the magnetic field from penetrating into the superconducting matter. This requires that the normal component of the magnetic field and the tangential components of the electric field have to vanish (Pons & Geppert 2007), i.e., we assume that B z = E x = E y = 0 at that interface. At the transition to a vacuum (z = +1), the analog to the toroidal component B y has to vanish, but the boundary conditions for the other components are not so simple.…”
Section: Basic Equations and Model Set Upmentioning
confidence: 99%
“…They correctly pointed out that Hall currents are able to create current sheets (which are sites for efficient dissipation) and that the evolution of the toroidal field resembles the Burgers equation. The same Burgers-like equation is applicable even to non-stratified media, but in a spherical shell (Pons & Geppert 2007), in which the Hall term in the induction equation tends to create current sheets instead of ordinary turbulence. Rheinhardt & Geppert (2002, hencefort RG) showed by a linear analysis that, in a one-component (electron) plasma, a large-scale background magnetic field may become unstable to smaller scale perturbations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation